A NEW APPROACH TO THE ASSESSMENT MALE SEXUALITY IN SYMPTOMATIC BENIGN PROSTATIC HYPERPLASIA (ROSTOV QUESTIONNAIRE) - A. Y. Kireev (Вестник урологии, 2013)
We developed a questionnaire to determine the male sexuality , which is determined by sexual history retrospectively in 105 patients aged 39 to 81 years. According to the results of the survey in a group of patients with normal sexuality included 33,33%, of the men in the group with reduced sexuality 35,24%, in the group with increased sexuality – 31,43% men. It was determined that the questionnaire can effectively divide the men by their level of sexuality. A number of trusted dependency between sexuality of patients with symptomatic BPH , and the following criteria: the severity of symptoms of the lower urinary tract , the average size of the prostate gland, PSA blood, testosterone levels. Separation of patients in terms of sexuality by the author questionnaire can serve as a tool to assess the main clinical manifestations of benign prostatic hyperplasia , and also identify early signs of hypogonadism .